Variation in Tacrolimus Trough Concentrations in Liver Transplant Patients Undergoing Endoscopic Retrograde Cholangiopancreatography: A Retrospective, Observational Study - Wang, Rongrong; Wang, Weili; Ma, Kuifen; Duan, Xin; Wang, Fangfang; Huang, Mingzhu; Zhang, Wei; Liang, Tingbo (Frontiers in Pharmacology, 2020)
Objective High variabilities in tacrolimus (TAC) exposure are still problems that confuse physicians. TAC trough levels (TAC Cmin) fluctuated considerably after endoscopic retrograde cholangiopancreatography (ERCP) treatment in several liver transplant (LT) patients. We aimed to investigate the variation regularity of TAC Cmin post-ERCP and related factors. Methods This study was a retrospective, observational study conducted at the First Affiliated Hospital of Zhejiang University in China. From October 2017 to January 2019, 26 LT patients that received ERCP were included (73 TAC Cmin measures). The absolute difference and the variation extent in TAC Cmin pre- and post-ERCP were analyzed. Patients were divided into mild and obvious variation groups, and the differences were compared. Results The TAC Cmin in LT patients significantly increased in the first three days post-ERCP (p<0.05) and increased by more than 20% in 18 out of 26 (69.2%) patients. The mean extent of variation in TAC Cmin was 45.1% (95% confidence interval [CI]: 28.3–81.3%) and 31.4% (95% CI: 9.7–53.1%) on days 1 and 3 post-ERCP, respectively. The increasing TAC Cmin gradually returned to baseline within a week (p>0.05). The daily TAC dose and total bile acid (TBA) level were significantly higher (p<0.05) in patients with obvious variation in TAC Cmin. The differences in other demographics, clinical characteristics, variation in laboratory data, and serum amylase levels between the two groups were not significant. Conclusion The TAC Cmin significantly increased in LT patients during the first three days after ERCP, and the level returned to baseline within a week. The daily TAC dose and TBA levels may be related to this increase. Frequent drug concentration monitoring should be executed in the early phase post-ERCP, especially in patients with related factors.